2019
DOI: 10.1186/s40635-019-0266-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the systemic inflammatory response on hepatic bacterial elimination in experimental abdominal sepsis

Abstract: Background Bacterial translocation from the gut has been suggested to induce a systemic inflammatory response syndrome (SIRS) and organ dysfunction. The liver has a pivotal role in eliminating circulating bacteria entering from the gut. We investigated whether pre-existing inflammation affects hepatic bacterial elimination. Methods Fifteen anaesthetised piglets were infused with E. coli in the portal vein for 3 h. The naive group ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Sepsis is defined as severe systemic inflammatory reaction, it contributes to multiple tissues and organ dysfunction, and the process is intricate [ 1 , 2 ]. Currently, the morbidity and mortality of sepsis remain high around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is defined as severe systemic inflammatory reaction, it contributes to multiple tissues and organ dysfunction, and the process is intricate [ 1 , 2 ]. Currently, the morbidity and mortality of sepsis remain high around the world.…”
Section: Introductionmentioning
confidence: 99%
“…In ESS this trapping mechanism may be more important than other bacterial removal processes. In the liver there is an active uptake of bacteria from the blood 23 , 24 and it has recently been shown that this uptake is reduced in secondary sepsis 25 , which might promote a lower bacterial growth in the liver. Particularly noteworthy is that the significant correlation between bacterial growth in the liver and spleen as demonstrated in PS, suggesting related control of the host defence mechanisms, is not observed in ESS despite reduced growth in the spleen and a similar trend in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Kupffer cells, macrophages present in the liver, efficiently phagocyte pathogens and PAMPs that enter the liver via arterial or portal circulation or translocation (migration of active bacteria or bacterial products Creatinine level mg/dl from the intestinal lumen to normal sterile tissue) has been known to induce and guard against systemic resistance. In animals infected with E. coli, the elimination of E. coli is slow, while the release of endotoxin is high so that it influences the hepatic and systemic circulation [4] . An increase in ALT can be caused by the direct effect of bacterial toxins, drugs, chemicals on liver cells, especially those that are closed to the central vein.…”
Section: Discussionmentioning
confidence: 99%